Efecto de la fluorhidrocortisona en pacientes con hipotensión arterial crónica - Tapia, Fernando A. (1973)
The effect of 9-alpha-fluorohy-drocortisone, a mineralocorticoid with minimal glucocorticoide activity, was studied in 40 patients with chronic or orthostatic arterial hypotension. The follow-up varied from 1 to 24 months. Periodic clinical ecaluation included blood pressure and puise measurements on lying, sitting and standing positions, a Schellong's postural test and weight variations. Serial determinations of serum electrolytes and urinary excretion of 17-ketosteroids and 17-hydroxycorticosteroids were also performed.  Marked improvement was observed in 25 patients (62.5%) and moderate improvement in 14 (35%). The Schellong's postural test was abnormal in 37 patients (92%) prior to therapy and became normal in 34 (85%) after treatment.The average initial dose of the drug was 0.2 mg. daily.  The rise on sytolic blood pressure and pulse pressure during treatment was statistically significant, specially on standing position (p<0.001). The tolerance to the drug was excellent, with minimal side effects in 9 patients: headache (5), edema (2), paresthesias (2), palpitations (2), thirsi, muscleaching, somnolence, anxiety (1). In 20 patients (50%) a slight increase on weight was observed (mean 1.298 Kg.). No significant  changes wer observed, hemoglobin, hematocrit and urinary excretion of steroids. The mechanism of its effect upon lying and orthostatic blood pressure, appears to be due to expanded plasma and extra cellular volume by sodium retention, increased peripheral vascular tone and increased vascular reactivity to endogenous pressor substances released on adopting the upríght position.  The effectiveness and tolerance of the 9-alpha-flurohydrocortisone justify its use in chronic hypotensive tates due to constitutional or acquired arterial hypotonia and in orthostatic circulatory disregulation, excluding acute cardiogenic and hypovolemic etiology.